FREQUENCY OF BLADDER, BOWEL AND SEXUAL DYSFUNCTION IN NMO. Issue 10 (9th September 2014) - Mutch, Kerry; Methley, Abigail; Zhao, Steven; Elsone, Liene; Emmanuel, Anton; Panicker, Jalesh; Jacob, Anu
Abstract : Background: The impairment of mobility due the severe myelitis in NMO is well known, but the effect on bladder, bowel and sexual function is not reported. We report the frequency of these problems in NMO. Method: 50 patients [42 females) with aquaporin-4 antibody positive NMO spectrum disorder, all with myelitis, were studied. They completed validated organ-specific questionnaires: Bladder Control Scale (BLCS), Bowel Control Scale (BWCS), Sexual Satisfaction Scale (SSS). Results: Bladder symptoms were reported in 78% and 44% experienced severely restricted lifestyle due to these. Similarly 80% had high bowel scores (54% constipation) and 24% experienced lifestyle impairment. Of the 29 patients in a relationship 12 (41%) were dissatisfied with their sexual life, four of five men had erectile dysfunction. Conclusion: This first ever report on the extent of pelvic organ dysfunction in NMO identified significant and oft hidden morbidity. The importance of assessment of these symptoms is emphasised by the availability of treatments for them. It also highlights the importance of treating and preventing relapses in NMO.